Antro-pyloro-duodenal motor responses to gastric and duodenal nutrient in critically ill patients. Issue 10 (29th May 2005) - Chapman, M; Fraser, R; Vozzo, R; Bryant, L; Tam, W; Nguyen, N; Zacharakis, B; Butler, R; Davidson, G; Horowitz, M
Abstract : Background: Gastric emptying is frequently delayed in critical illness which compromises the success of nasogastric nutrition. The underlying motor dysfunctions are poorly defined. Aims: To characterise antro-pyloro-duodenal motility during fasting, and in response to gastric and duodenal nutrient, as well as to evaluate the relationship between gastric emptying and motility, in the critically ill. Subjects: Fifteen mechanically ventilated patients from a mixed intensive care unit; 10 healthy volunteers. Methods: Antro-pyloro-duodenal pressures were recorded during fasting, after intragastric administration (100 ml; 100 kcal), and during small intestinal infusion of liquid nutrient (6 hours; 1 kcal/min). Gastric emptying was measured using a 13 C octanoate breath test. Results: In healthy subjects, neither gastric nor small intestinal nutrient affected antro-pyloro-duodenal pressures. In patients, duodenal nutrient infusion reduced antral activity compared with both fasting and healthy subjects (0.03 (0–2.47) waves/min v 0.14 (0–2.2) fasting (p = 0.016); and v 0.33 (0–2.57)/min in healthy subjects (p = 0.005)). Basal pyloric pressure and the frequency of phasic pyloric pressure waves were increased in patients during duodenal nutrient infusion (3.12 (1.06) mm Hg; 0.98 (0.13)/min) compared with healthy subjects (−0.44 (1.25) mm Hg; p<0.02 after 120 minutes; 0.29 (0.15)/min; p = 0.0002) and with fasting (−0.06 (1.05) mm Hg; p<0.03 after 160 minutes; 0.49 (0.13)/min; (p = 0.0001). Gastric emptying was delayed in patients (gastric emptying coefficient 2.99 (0.2) v 3.47 (0.1); p = 0.015) and inversely related to the number of pyloric pressure waves ( r = −0.563, p = 0.029). Conclusions: Stimulation of pyloric and suppression of antral pressures by duodenal nutrient are enhanced in the critically ill and related to decreased gastric emptying.